Strategi Sekolah Mengatasi Pelanggaran Tata Tertib Sekolah dalam Membentuk Karakter Disiplin Siswa di Mas At-Taqwa Beru - Fathia Aulia Muthmainna (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
Based on the results of research related to school strategies in dealing with violations of rules and regulations to improve the disciplinary character of students at MAS AT-TAQWA Beru, it can be concluded as follows: The strategy implemented by the school consists of three approaches, namely (1) Preventive strategy, which includes outreach to students , habituation, and extracurricular activities as prevention efforts before violations occur, (2) Repressive strategies, which are implemented after violations occur, including providing advice, sanctions, and supervision, and (3) Curative strategies, which focus on coaching students and summoning parent. The obstacles faced by schools in overcoming violations of discipline and forming students' disciplinary character include (1) Internal factors, which include limited school facilities and infrastructure as well as the condition of the students themselves, and (2) External factors, namely the influence of the family environment, especially in cases of families that are not intact (broken homes) or parents who are busy working, so that children often live with grandparents and receive less attention, as well as the influence of playmates and the living environment.